Serological Evidence of Human Infection with Avian Influenza A H7virus in Egyptian Poultry Growers - Gomaa, Mokhtar R.; Kandeil, Ahmed; Kayed, Ahmed S.; Elabd, Mona A.; Zaki, Shaimaa A.; Abu Zeid, Dina; El Rifay, Amira S.; Mousa, Adel A.; Farag, Mohamed M.; McKenzie, Pamela P.; Webby, Richard J.; Ali, Mohamed A.; et al. (PloS one, 2016)
Avian influenza viruses circulate widely in birds, with occasional human infections. Poultry-exposed individuals are considered to be at high risk of infection with avian influenza viruses due to frequent exposure to poultry. Some avian H7 viruses have occasionally been found to infect humans. Seroprevalence of neutralizing antibodies against influenza A/H7N7 virus among poultry-exposed and unexposed individuals in Egypt were assessed during a three-years prospective cohort study. The seroprevalence of antibodies (titer, ≥80) among exposed individuals was 0%, 1.9%, and 2.1% annually while the seroprevalence among the control group remained 0% as measured by virus microneutralization assay. We then confirmed our results using western blot and immunofluorescence assays. Although human infection with H7 in Egypt has not been reported yet, our results suggested that Egyptian poultry growers are exposed to avian H7 viruses. These findings highlight the need for surveillance in the people exposed to poultry to monitor the risk of zoonotic transmission of avian influenza viruses.